2020
DOI: 10.1039/d0ra02796k
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the local electrical properties of crystalline and amorphous domains in electrochemically doped conjugated polymer thin films

Abstract: The effects of electrochemical doping on the local domain properties of conjugated polymer films are investigated. Nanoscale crystalline domains are most affected by doping and have a higher degree of doping compared to amorphous domains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 58 publications
0
18
0
Order By: Relevance
“…A recent study on the semiconducting polymer P3HT, containing both amorphous and crystalline domains, showed that chemical doping tends to soften the crystalline domains. [31] The doped crystalline domains in P3HT show a reduced modulus, and their co-existence with amorphous domains in the film causes the spatial modulus histogram in doped P3HT to show a double peak feature. [31] C14-PBTTT films have large semicrystalline terraces, and when chemically doped, shows a spatial modulus histogram that has a single peak.…”
Section: Peakforce Qnm Based Nanomechanical Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study on the semiconducting polymer P3HT, containing both amorphous and crystalline domains, showed that chemical doping tends to soften the crystalline domains. [31] The doped crystalline domains in P3HT show a reduced modulus, and their co-existence with amorphous domains in the film causes the spatial modulus histogram in doped P3HT to show a double peak feature. [31] C14-PBTTT films have large semicrystalline terraces, and when chemically doped, shows a spatial modulus histogram that has a single peak.…”
Section: Peakforce Qnm Based Nanomechanical Characterizationmentioning
confidence: 99%
“…[31] The doped crystalline domains in P3HT show a reduced modulus, and their co-existence with amorphous domains in the film causes the spatial modulus histogram in doped P3HT to show a double peak feature. [31] C14-PBTTT films have large semicrystalline terraces, and when chemically doped, shows a spatial modulus histogram that has a single peak. Figure 4a shows a comparison of the spatial modulus measured on a pristine C14-PBTTT film compared with a C14-PBTTT film that was chemically doped to high conductivities up to 1000 S cm −1 using an ion exchange based doping process (see Section S5, Supporting Information).…”
Section: Peakforce Qnm Based Nanomechanical Characterizationmentioning
confidence: 99%
“…Our previous research concluded that, for e-doped RR-P3HT thin films, dopant concentration is predominantly higher in crystalline domains compared to amorphous ones. 35 Because RRa-P3HT thin films are more amorphous compared to the RR-P3HT thin films, the doping intensity after e-doping is expected to be lower for RRa-P3HT thin films. The lower doping intensity in RRa-P3HT thin films would correspond to lower dopant concentrations, compared to RR-P3HT thin films.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Combined with the high charge density required for electrochemical doping, this often yields heterogeneous potential energy landscapes in the OMIEC, where different regions or domains of a single active layer can vary greatly in terms of their electroactivity and charge transport properties. In some cases, heterogeneity occurs over extremely small length scales comprising only a few chromophore segments, which greatly limits the utility of conventional characterization techniques that rely on longer-range order and/or periodicity (e.g., X-ray and scanning probe methods ) for understanding the doping process. It is therefore necessary to develop new approaches for capturing the dynamic picture underlying electrochemical doping to provide a molecular description of charged states in weakly coupled, structurally irregular, and heterogeneous polymer-electrolyte systems.…”
Section: Introductionmentioning
confidence: 99%